Transition to turbulence in Hunt's flow in a moderate magnetic field. (21st September 2016) - Braiden, L.; Krasnov, D.; Molokov, S.; Boeck, T.; Bühler, L.
Abstract: Pressure-driven magnetohydrodynamic duct flow in a transverse uniform magnetic field is studied by direct numerical simulation. The electric boundary conditions correspond to Hunt's flow with perfectly insulating walls parallel to the magnetic field (sidewalls) and perfectly conducting walls perpendicular to the magnetic field (Hartmann walls). The velocity distribution exhibits strong jets at the sidewalls, which are susceptible to instability even at low Reynolds numbers Re . We explore the onset of time-dependent flow and transition to states with evolved turbulence for a moderate Hartmann number . At low Re time-dependence appears in the form of elongated Ting-Walker vortices at the sidewalls of the duct, which, upon increasing Re, develop into more complex structures with higher energy and then the sidewall jets partially detach from the walls. At high values of Re jet detachments disappear and the flow consists of two turbulent jets and nearly laminar core. It is also demonstrated that, there is a range of Re, where Hunt's flow exhibits a pronounced hysteresis behavior, so that different unsteady states can be observed for the same flow parameters. In this range multiple states may develop and co-exist, depending on the initial conditions.